Effect of Financial Ratio on Return of Shares on LQ45 Companies Listed on Indonesia Stock Exchange: Pengaruh Rasio Keuangan Terhadap Return Saham Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia - Romlina Romlina; Syahril Effendi (Perkumpulan Doktor Indonesia Maju, 2020)
The purpose of this study was to determine the Effect of Financial Ratios on Stock Returns on LQ45 Companies Listed on the Indonesia Stock Exchange. The independent variables used are Financial Ratios. The dependent variable used is Stock Return. The population in this study is the Current Ratio, Return on Equity, Debt to Equity Ratio, and Stock Return data on LQ45 companies listed on the Indonesia Stock Exchange for 5 years from 2015-2019. The sample in this study is LQ45 companies listed on the Indonesia Stock Exchange (IDX). Data analysis techniques in this study include multiple linear regression. The test results in this study indicate that the Current Ratio variable has no significant effect on Stock Return. From the results of testing the variables above, the Current Ratio shows the calculated T value of -0.242 T value of the table 2.016 with a significance number 0.810> 0.05. The Return on Equity variable influences the Stock Return. From the results of testing the variables above, Return on Equity shows that the calculated T value of 2.232> T table value of 2.016 with a significance number of 0.031 <0.05. Debt to Equity Ratio variable has a significant effect on Stock Return. From the results of testing the variables above, Debt to Equity Ratio shows that the calculated T value of 5.923> T table value of 2.016 with a significance number of 0.000 <0.05. Current Ratio, Return on Equity, and Debt to Equity Ratio together have a significant effect on Stock Returns with the number that a significant value of 0,000 <0.05 and an F count of 14.498> F table of 3.21.